P22-17 Cell mechanisms induced by doxorubicin-loaded UCNP@MSN nanoparticles with a thermos-responsive nanovalve in melanoma cells - P. Oskoei; L.-M. Keller; E. Anderson; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2025)

P01-46 Effects of doxorubicin-loaded UCNP@MSN core-shell particles with a thermoresponsive nanovalve in melanoma cells - P. Oskoei; J. Nogueira; L.-M. Keller; E. Andresen; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2024)

OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

Respiratory syncytial virus-associated hospitalization rates in high-risk populations: an observational comparative cohort analysis - B. Resch; C. Puchas; B. Urlesberger (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Respiratory syncytial virus associated hospitalizations in preterm infants of 29 to 32 weeks gestational age using a risk score tool for palivizumab prophylaxis - B. Resch; V. S. Bramreiter; S. Kurath-Koller; T. Freidl; B. Urlesberger (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Physiology of the Vc-NhaP paralogous group of cation–proton antiporters in Vibrio cholerae - Muntahi Mourin; Carla B. Schubiger; Craig T. Resch; Claudia C. Häse; Pavel Dibrov (Molecular and Cellular Biochemistry, 2017)

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes - Emily B. Graham; Alex R. Crump; Charles T. Resch; Sarah Fansler; Evan Arntzen; David W. Kennedy; Jim K. Fredrickson; James C. Stegen (Environmental Microbiology, 2017)
Summary Subsurface groundwater‐surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically‐connected, physicochemically‐distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these patterns; (c) groups of organisms that corresponded to deterministic changes in the environment; and (d) correlations between these groups and hyporheic metabolism. All microbiomes remained dissimilar through time, but consistent presence of similar taxa suggested dispersal and/or common selective pressures among zones. Further, we demonstrated a pronounced impact of deterministic assembly in all microbiomes as well as seasonal shifts from heterotrophic to autotrophic microorganisms associated with increases in groundwater discharge. The abundance of one statistical cluster of organisms increased with active biomass and respiration, revealing organisms that may strongly influence hyporheic biogeochemistry. Based on our results, we propose a conceptualization of hyporheic zone metabolism in which increased organic carbon concentrations during surface water intrusion support heterotrophy, which succumbs to autotrophy under groundwater discharge. These results provide new opportunities to enhance microbially‐explicit ecosystem models describing hyporheic zone biogeochemistry and its influence over riverine ecosystem function.

Respiratory syncytial virus-associated hospitalizations over three consecutive seasons in children with congenital heart disease - B. Resch; S. Kurath-Koller; J. Hahn; W. Raith; M. Köstenberger; A. Gamillscheg (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Prospective evaluation of clinical scoring systems in infants with bronchiolitis admitted to the intensive care unit - S. Rödl; B. Resch; N. Hofer; I. Marschitz; G. Madler; E. Eber; G. Zobel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Two nosocomial norovirus outbreaks in the neonatal intensive and intermediate care unit - C. Sommer; W. Mueller; B. Resch (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Observational study of respiratory syncytial virus-associated hospitalizations and use of palivizumab in premature infants aged 29–32 weeks - B. Resch; W. Gusenleitner; W. D. Müller; J. Haas (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

How to Improve Quality Assurance in Fluorometry: Fluorescence-Inherent Sources of Error and Suited Fluorescence Standards - U. Resch-Genger; K. Hoffmann; W. Nietfeld; A. Engel; J. Neukammer; R. Nitschke; B. Ebert; R. Macdonald (Journal of Fluorescence, 2005)

Traceability in Fluorometry: Part II. Spectral Fluorescence Standards - U. Resch-Genger; D. Pfeifer; C. Monte; W. Pilz; A. Hoffmann; M. Spieles; K. Rurack; J. Hollandt; D. Taubert; B. Schönenberger; P. Nording (Journal of Fluorescence, 2005)

Typical Frankia infect actinorhizal plants exotic to New Zealand - Michael L. Clawson; David R. Benson; Steven C. Resch; David W. Stephens; Warwick B. Silvester (New Zealand Journal of Botany, 1997)
Frankia strains are actinomycetes that fix N 2 in root nodules of plants classified in eight families of the Angiospermae. The wide variety of plants infected has raised questions about the ecology and diversity of Frankia symbionts, and their co‐evolution with actinorhizal plants. Partial sequencing was done of the small subunit (16S) rRNA gene from Frankia endophytes present in the root nodules of Alnus cordata , A. glutinosa , A. viridis , Casuarina equisetifolia, Coriaria arborea, C. plumosa , and Elaeagnus pungens growing in New Zealand. With the exceptions of the Coriaria spp., all of the plants are exotic to New Zealand. Analysis of the 16S rRNA gene indicates that the exotic species were nodulated by Frankia strains that cluster with strain groups previously shown to be typical for each actinorhizal host. Frankia in 12 native Coriaria spp. nodules yielded two sequences differing in only one position, suggesting a relatively low diversity compared with the exotic species.